The threat against man and the reaction of the Christian - An economic viewpoint* - Wyk, L. A. van (Koers, 1978)
I refer here to the study on trade boycotts that I undertook on behalf of the Institute for the Advancement of Calvinism and on which this paper is largely based. When I have to discuss the subject of threatened man as seen from an economic angle, this theme would have been somewhat negative, should one not look further than the threat alone. Therefore it is more positive to discuss the challenges of present-day man. This remains my viewpoint throughout: View the economic phenomena realistically and identify the threat therein, but do not allow the threats of today ever to become more than the challenges of tomorrow and never forget — not only are there threats, but so also are there many more opportunities which we ought to avail ourselves of through our abilities.